Changing handedness after nerve reconstruction in brachial plexus birth palsy - Yao, Chenglun; Song, Jie; Sun, Jiayu; Tang, Weijun; Chen, Liang; Gu, Yudong (Frontiers in Neurology, 2024)
Purpose Right obstetric brachial plexus injuries (OBPI) often lead to left-handedness before limb function is restored post-surgery. A pertinent question arises about promoting a transition from left to right-handedness. We hypothesized that, with the decrease in neuroplasticity, handedness switching is not only difficult, but also reduces handedness-speech lateralization, impaired motor adaptability, and compromised language proficiency. Methods We retrospectively analyzed clinical data from January 1996 to January 2012 at our hospital. Participants were divided into intervention or control groups based on handedness switching. We compared handedness and computed lateral quotient (LQ) and lateralization index (LI) for handedness-speech center. Additionally, we assessed dominant hand’s writing speed, language function, and IQ. Associations between absolute LI and LQ values, writing speed, language scores, and IQ were examined. Results Nineteen extended Erb’s palsy participants were enrolled, eight in the intervention group, and 11 in the control. No right-handed individuals were found in either cohort. The intervention group had significantly lower LQ and LI values, and fewer achieved normal writing speed. Yet, no notable disparities in language scores or IQ emerged. Notably, we established correlations between motor finesse, handedness degree, and handedness-speech lateralization. Conclusion For right extended Erb’s palsy, shifting handedness is nearly unfeasible, and such an endeavor could trigger a reduction in handedness-speech lateralization magnitude and diminished motor finesse.